2021
DOI: 10.1139/cjz-2020-0284
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of gilthead seabream (Sparus aurata) juvenile dentition as a tool to assess the effect of diet

Abstract: Gilthead seabream, Sparus aurata Linnaeus, 1758 (Perciformes, Sparidae), is an important aquaculture species in the Mediterranean Sea basin. Yet, quantitative data on its dentition under standard farming conditions are currently lacking. It is furthermore unknown if the dentition can adapt to food of different sizes. Here, we describe the lower jaw dentition of juvenile S. aurata fed a standard pellet size (4 mm), and present a detailed analysis of eleven representative teeth. Overall, the number of teeth show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Data of dentition analysis recently conducted on seabream, showed that large pellet size tended to produce fish with the lowest number of teeth on the dentary, while specimens fed with small pellet size presented the smallest teeth area. However, no significant differences were found in general dentition among fish fed with the three different pellet sizes (de Azevedo et al, 2021).…”
Section: Discussionmentioning
confidence: 73%
“…Data of dentition analysis recently conducted on seabream, showed that large pellet size tended to produce fish with the lowest number of teeth on the dentary, while specimens fed with small pellet size presented the smallest teeth area. However, no significant differences were found in general dentition among fish fed with the three different pellet sizes (de Azevedo et al, 2021).…”
Section: Discussionmentioning
confidence: 73%
“…Finally, a puzzling question is how to explain tooth replacement where one large replacement tooth replaces two or more smaller ones, as is observed in species with large molariform teeth [e.g. in the cichlid Astatoreochromis alluaudi and the sea bream Sparus aurata (Huysseune, 1995; de Azevedo et al ., 2021)]. We currently do not know if replacement is repressed in one predecessor, if one germ develops at the expense of the other, or if both predecessors are replaced nevertheless and teeth simply occupy an enlarged surface due to expansion of the bone surface.…”
Section: The Micro‐anatomical Setting Of Teleost Tooth Replacementmentioning
confidence: 99%
“…Classical studies about tooth replacement are mainly interested in the question of how patterns are set up (timing and sequence of formation of first‐generation teeth), whether these patterns are maintained, and how fast the teeth cycle. These studies utilised traditional approaches, such as examination of preserved material (Motta, 1984), wax impressions (Berkovitz & Moore, 1974, 1975), serial sections and two‐dimensional or three‐dimensional reconstructions (Berkovitz, 1977 b ; Berkovitz & Shellis, 1978; Abduweli et al ., 2014), cleared and stained preparations (Lawson & Manly, 1973; Van der heyden, Wautier & Huysseune, 2001; Trapani, Yamamoto & Stock, 2005; de Azevedo et al ., 2021), scanning electron micrographs (Motta, 1984), radiographs (Berkovitz, 1975; Berkovitz & Shellis, 1978; Witten, Hall & Huysseune, 2005; Huysseune, Hall & Witten, 2007), and injection of fluorochromes (Bergot, 1975; Huysseune, 1989; Abduweli et al ., 2014; Ellis et al ., 2015) (Fig. 1A–D).…”
Section: Introductionmentioning
confidence: 99%